ANALISIS KETERAMPILAN LITERASI SAINS SISWA KELAS XI PADA MATA PELAJARAN BIOLOGI MENGGUNAKAN INSTRUMEN TOSLS - Nur Fatimah; Aidil Adhani; Silfia Ilma (Borneo Journal of Biology Education (BJBE), 2025)
Scientific literacy is being able to understand scientific concepts and principles. It invoves using skills, attitudes, and khowledge, and making decisions based on the khowledge that has been acquired. The present research aimed to determine the scientific literacy skills of Muhammadiyah Tarakan High School students using TOSLS instrumen. This research was TOSLS (Test of Scientific Literacy Skills) in the form of a multiple-choice test. The sample consisted of all students in class XI MIA of SMA Muhammadiyah Tarakan. The research result showed that the skills aspect of understanding the investigation method that leads to scientific knowledge was 51.54% classified into very poor category. The skills aspect of organizing, analysing, and interpreting quantitative data and scientific information was 71.50% classified onto fair category. The mean score of both aspects was 61.47% classified into fair category. Based on the result of data analysis, it indicated that the students were more likely to have skills in managing quantitative data compared to understanding scientific methode because skills in managing quantitative data were more often used in learning than understanding scientific steps. This was proven by the percentage result of the second aspect which was higher than that of the first aspect. The recommendation that can be offered in this research is that the learning process is axpected to give more emphasis on the skills aspect in understanding investigation method and scientific kjowledge. It is suggested that the learning should be more emphasis on the skills aspect of understanding investigation method that leads to scientific literacy skills.